Ensino e a aprendizagem de matemática: - SILVA, Alessandro Carvalho da (Universidade Federal do Tocantins, 2023)
What activities are currently available to work with the various groups of students that are able to overcome the difficulties encountered in the teaching and learning process of mathematics? With this guiding question, the main goal was to know and analyze new educational activities capable of assisting the teacher in the teaching of mathematics in basic education for all students. The specific objectives are: to expose new methodologies to teachers, to contribute to the acquisition of knowledge about activities aimed at students that need differentiated care, to show that activities considered simple can make a lot of difference in students' learning. Regarding the methodology, we initially carried out a bibliographic research, followed by a qualitative analysis of the information obtained. In the course of the theoretical reference, a selection of activities proposed for the teacher in the teaching and learning process of his students was presented. There are group and individual activities, face- to-face and online activities. Through the research carried out for the elaboration of this work it was verified how vast is the field of recreational activities geared towards the teaching of mathematics. Through them teachers can diversify their classes making them appreciated and, with it, more participatory.